Kinerja Lemari Pendingin Alami yang digunakan Sesuai Kondisi Cuaca di Kota Medan - Sitorus, Tulus Buhanuddin; Arianil, Farida; Sitepu, Tekad (JURNAL PENDIDIKAN TEKNOLOGI DAN KEJURUAN, 2017)
One application in a direct evaporative cooling system was a natural cooler. The advantages of this system were not using the electrical energy and so far also environmentally. This research aims to obtain a performance analysis of the natural cooler as a store for vegetables and fruits in Medan city. The materials for natural cooler consists of teak wood and gunny. The experiments were conducted during seven days in the open air, which were exposed to the solar radiation. The parameter measurement on the weather was using HOBO devices and to record the temperature changes for vegetables or even fruits is using its acquisition data. The results showed that the maximum efficiency of the natural cooler could be obtained  for 43.79%  in the average air temperature of 30.51oC, the air humidity average is 85.12%  with  average solar radiation of 183.98 W/m2.  Experimental data were showing that the condition of  freshness on vegetables or even on  fruits was heavily influenced by weather conditions